An assessment of the use of ocean gliders to undertake acoustic measurements of zooplankton: the distribution and density of Antarctic krill (Euphausia superba) in the Weddell Sea. (10th June 2014) - Guihen, Damien; Fielding, Sophie; Murphy, Eugene J.; Heywood, Karen J.; Griffiths, Gwyn
<x xml:space="preserve">Abstract</x> A calibrated 120 kHz single‐beam echo‐sounder was integrated into an ocean glider and deployed in the Weddell Sea, Southern Ocean. The glider was deployed for two short periods in January 2012, in separate survey boxes on the continental shelf to the east of the Antarctic Peninsula, to assess the distribution of Antarctic krill (Euphausia superba). During the glider missions, a research vessel undertook acoustic transects using a calibrated, hull‐mounted, multi‐frequency echo‐sounder. Net hauls were taken to validate acoustic targets and parameterize acoustic models. Krill targets were identified using a thresholded schools analysis technique (SHAPES), and acoustic data were converted to krill density using the stochastic distorted‐wave Born approximation (SDWBA) target strength model. A sensitivity analysis of glider pitch and roll indicated that, if not taken into account, glider orientation can impact density estimates by up to 8‐fold. Glider‐based, echo‐sounder—derived krill density profiles for the two survey boxes showed features coherent with ship‐borne measurements, with peak densities in both boxes around a depth of 60 m. Monte Carlo simulation of glider subsampling of ship‐borne data showed no significant difference from observed profiles. Simulated glider dives required at least an order of magnitude more time than the ship to similarly estimate the abundance of krill within the sample regions. These analyses highlight the need for suitable sampling strategies for glider‐based observations and are our first steps toward using autonomous underwater vehicles for ecosystem assessment and long‐term monitoring. With appropriate survey design, gliders can be used for estimating krill distribution and abundance.